The moderating role of spirituality and gender in Canadian and Iranian emerging adolescents’ theory of mind and prosocial behavior - Khalili, Nadia; Bosacki, Sandra; Talwar, Victoria (Frontiers in Psychology, 2023)
Introduction While research has found a link between ToM and prosociality in terms of caring and helping others which may also vary across cultures, the moderating role of spirituality and culture of this association in emerging adolescence has received little attention. Methods The current study empirically “examined” the role of spirituality and gender in relation to ToM and prosocial behavior in Canadian and Iranian emerging adolescents. A total of 300 (153 girls) emerging adolescents (M = 11.502, SD = 2.228) were recruited from Montreal, Canada and Karaj, Iran. A series of double moderation analysis and ANOVA was conducted. Results and discussion Results indicated the difference between direct and indirect influences of ToM and its interactions with culture, gender, and spirituality on prosocial behavior. This implies an emerging complex framework which suggests the dynamic nonlinear interactions between these factors. Implications for youth’s social-emotional understanding will be discussed.